Developmental lineage of human pluripotent stem cell‐derived cardiac fibroblasts affects their functional phenotype. Issue 9 (2nd August 2021) - Floy, Martha E.; Givens, Sophie E.; Matthys, Oriane B.; Mateyka, Taylor D.; Kerr, Charles M.; Steinberg, Alexandra B.; Silva, Ana C.; Zhang, Jianhua; Mei, Ying; Ogle, Brenda M.; McDevitt, Todd C.; Kamp, Timothy J.; et al.
Abstract: Cardiac fibroblasts (CFBs) support heart function by secreting extracellular matrix (ECM) and paracrine factors, respond to stress associated with injury and disease, and therefore are an increasingly important therapeutic target. We describe how developmental lineage of human pluripotent stem cell‐derived CFBs, epicardial (EpiC‐FB), and second heart field (SHF‐FB) impacts transcriptional and functional properties. Both EpiC‐FBs and SHF‐FBs exhibited CFB transcriptional programs and improved calcium handling in human pluripotent stem cell‐derived cardiac tissues. We identified differences including in composition of ECM synthesized, secretion of growth and differentiation factors, and myofibroblast activation potential, with EpiC‐FBs exhibiting higher stress‐induced activation potential akin to myofibroblasts and SHF‐FBs demonstrating higher calcification and mineralization potential. These phenotypic differences suggest that EpiC‐FBs have utility in modeling fibrotic diseases while SHF‐FBs are a promising source of cells for regenerative therapies. This work directly contrasts regional and developmental specificity of CFBs and informs CFB in vitro model selection.